DEVELOPING WRITING TEST FOR EFL LEARNERS - Ningrum, Ary Setya Budhi (Jurnal Bahasa Lingua Scientia, 2011)
This paper tries to present a general review of testing writing in English as a foreign language. This paper covers some of the important and relevant aspects of developing writing test such as definition of writing, writing in ESL/EFL classroom, writing assessment, and validating writing test. Special review is addressed to give a brief note of a comprehensive and step-by-step procedure of developing test instrument proposed by Prof. Soenardi Djiwandono.